2010
DOI: 10.1111/j.1439-0523.2009.01652.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation for saturated fatty acid content in a collection of European winter oilseed rape material (Brassica napus)

Abstract: Oil quality is an important issue in oilseed rape breeding programmes. Recently, the seed oil content of saturated fatty acids has received substantial interest, because in a number of industrialized countries dietary recommendations not only limit total fat intake but also intake of saturated fatty acids. The aim of the present study was to analyse the genetic variation for saturated fatty acid content in two sets of modern winter oilseed rape cultivars (Brassica napus L.) tested in field experiments under ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…Elektra. These results agreed with the findings of Dimov and Möller (2010) [28] that tested modern winter oilseed rape cultivars including cv. NK Fair and cv.…”
Section: Resultssupporting
confidence: 93%
“…Elektra. These results agreed with the findings of Dimov and Möller (2010) [28] that tested modern winter oilseed rape cultivars including cv. NK Fair and cv.…”
Section: Resultssupporting
confidence: 93%
“…Several authors have successfully determined specific parameters in rapeseed using mathematical and statistical methods based on the NIRS raw spectra; this success is important for the processing industry and the consumer . The NIRS procedure was used with the goal of finding an accurate, fast, environmentally friendly and cost‐efficient method for parameter assessment in rapeseed.…”
Section: Resultsmentioning
confidence: 99%
“…Using high erucic acid B. napus, Nath et al (2009) found that OC was significantly negatively correlated with oleic acid and positively correlated with ERU; the significant positive correlation between OC and ERU were also confirmed by Klassen (1976). While Mollers and Schierholt (2002), Zhao et al (2008), and Dimov and Mollers (2010) observed a positive correlation between OC and OLE using low erucic acid B. napus, a Pearson's correlation analysis of quality traits showed that OC had a significantly (P < 0.01) negative correlation with OLE and a positive correlation with ERU (Table 4). These results were in accordance with those of some previous reports (Klassen, 1976;Nath et al, 2009;Abideen et al, 2013) and inconsistent with those of others (Mollers and Schierholt, 2002;Zhao et al, 2008;Dimov and Mollers, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Mollers and Schierholt (2002), Zhao et al . (2008)and Dimov and Mollers (2010) used zero erucic acid material, while Nath et al . (2009) and Abideen et al .…”
Section: Discussionmentioning
confidence: 99%